Nursing entrepreneurship: motivations and possibilities for nursing entrepreneurs (Research, Society and Development, 2020)
Introduction: The resolution COFEN n° 0568/2018 regulates the nursing offices and clinics operations being a new possibility of acting as nurse in the business marketing that is passing by an economical and political crisis driven by rising unemployment. Goal: Analysis on literature the field action of nurses in the entrepreneurship nursing. Methods: It's about a bibliographical literature revision, written with an qualitative approach. The searching strategy was realized on March, 2020 through online database. PUBMED, SciELO LILACS and BDENF. The following health descriptions were used: intrapreneurial, entrepreneurship, entrepreneurs, entrepreneurialism, entrepreneurship initiative, nursing and service organizations, nursing and nurses. They were included in search: fully articles available for free, Portuguese, English and Spanish idioms. They were excluded doubled articles, theses and dissertations. It was reached a sample of 15 studies to be judiciously analysed. Results: to get a better data approach they were emerged with the following thematic categories: Profile of entrepreneur nurse; Causes and aspirations that took out the nurse to business; entrepreneurship field of action and business variety; Difficulties and variations to nursing business entrepreneurship; entrepreneurship through the academic formation. Final Considerations: It is concluded that this search the business entrepreneurship looks like and innovative area of actuation to the nurse in business marketing being able to have itself professional independence beyond concept development to encourage students and health area professionals nurses to potencialize, improve and strengthen entrepreneur actions as an option of professional growing.